Drying kinetics and quality changes during drying of red pepper - Di Scala, Karina Cecilia (2008)
A mathematical model is proposed to simulate the process of drying of individual pieces of red pepper under constant external conditions and to predict changes in some nutritional and organoleptic attributes of the product. The model was solved numerically to obtain moisture content and temperature as well as ascorbic acid and carotenoids concentration in the product as a function of time. A good agreement between predictions and experimental data at different drying temperatures was obtained. Water sorption isotherms of red pepper were determined in the range 20-50 °C and represented by two different sorption equations. Drying kinetics were represented by a diffusive model, the effective moisture diffusivity ranging from 5.01 to 8.32×10-10 m2/s with an activation energy of 23.35 kJ/mol. Degradation kinetics for ascorbic acid and total carotenoids were measured in the range 50-70 °C and modelled as first-order reactions. The rate constants increased with temperature and product moisture content. Average activation energies for carotenoids and vitamin C degradation were 50.1 and 26.9 kJ/mol, respectively. © 2007 Swiss Society of Food Science and Technology.